Analysis of factors affecting rehospitalization of patients with chronic kidney disease after educational hospitalization - Kose E; An T; Kikkawa A; Matsumoto Y; Hayashi H (Dove Medical Press, 2014)
Eiji Kose,1 Taesong An,2 Akihiko Kikkawa,2 Yoshiaki Matsumoto,3 Hiroyuki Hayashi1 1Department of Pharmacotherapy, School of Pharmacy, Nihon University, Funabashi, 2Yokosuka Kyousai Hospital, Yokosuka, 3Department of Clinical Pharmacokinetics, School of Pharmacy, Nihon University, Funabashi, Japan Background: Chronic kidney disease (CKD) is associated with a high risk of cardiovascular disease complications. Therefore, medical institutions conduct educational hospitalization for early treatment and education of CKD patients. However, patients who have been discharged after achieving educational targets can end up showing poor symptoms at home. There also have been several cases of rehospitalization or disease aggravation. In this study, we analyzed rehospitalized patients who were discharged from the hospital after CKD educational hospitalization and investigated the purpose of analyzing rehospitalization factors. Materials and methods: This was an observational case-control study conducted at Yokosuka Kyousai Hospital. We performed univariate analysis using patient background features and laboratory data between a rehospitalization group and a no-rehospitalization group. Next, we performed multiple logistic regression analysis using the results of the univariate analysis. Results: From the results of this study, we identified independent risk factors, such as serum albumin level, heart-failure complications, and estimated glomerular filtration rate (eGFR). Moreover, the serum Alb level was identified as the most important risk factor for rehospitalization. Therefore, we considered that it is important to live a life that makes it possible to maintain CKD stage G3b for a long time after discharge, because the cutoff level of eGFR is 31 mL/minute/1.73 m2. Conclusion: We believe that it is important to educate patients, their families, and medical staff on the importance of early detection and treatment, and we consider that this approach is important to inclusively protect the kidney. Keywords: albumin, glomerular filtration rate, cardiovascular disease, stages of chronic kidney disease